Molecular Identification of Microalgae BTM 11 and its Lectin Isolation, Characterization, and Inhibition Activity - Mustopa, Apon Zaenal; Isworo, Rhestu; Nurilmala, Mala; Susilaningsih, Dwi (Annales Bogorienses, 2016)
BTM 11 is unknown species of microalgae which has active compounds that can inhibit viruses. Lectin is a carbohydrate-binding protein that is found in microalgae with antiviral and antibacterial activities. The purpose of this study was to perform identification, isolation, characterization, and assay of lectin inhibitory activity of microalgae BTM 11. The result shows that microalgae BTM 11 has homology with Cyanobacterium (99%) and Geitlerinema sp (98%). Lectin of microalgae BTM 11 has molecular weight of 17 kDa. Lectin protein activity of microalgae BTM 11 was able to inhibit the enzyme activity of RNA helicase hepatitis C by 57.90% and 27.55%. In addition, the protein was able to suppress the activity of Staphylococcus aureus ATCC 6538, E. coli EPEC K.1.1. and Salmonella typhii ATCC 25241. Activitiy of lectin was stable at 30 °C and unaffected by the action of the enzyme. These results indicate that lectin of microalgae BTM 11 could be an alternative to antiviral and antibacterial proteins.